Gap Strategi Pencegahan Penyalahgunaan Obat : Studi Kasus Wilayah yang Minim Peran BNN dan BK - Winda Noviana; Feida Noorlaila Isti’adah (Jurnal Bintang Pendidikan Indonesia, 2025)
Drug abuse is a serious issue that affects public health, social dynamics, and the economy in various regions. In areas with limited roles of the National Narcotics Agency (BNN) and Guidance and Counseling (BK), preventive strategies are often suboptimal, creating gaps in mitigation efforts. This study aims to identify the gaps in drug prevention strategies in such areas, focusing on causal factors, challenges, and opportunities for improvement. The methods employed include literature reviews and interviews with community members and relevant stakeholders. The results indicate that the lack of human resources, limited access to education, and low public awareness are the primary challenges. Recommended strategies include empowering local communities, enhancing educational institutions' roles, and fostering cross-sector collaboration to strengthen prevention efforts in regions where the roles of BNN and BK are constrained.